MEDIA DIGITAL SEBAGAI AGORA BARU PEWARTAAN GEREJA DALAM SEMANGAT KNOW, SHARE, MEET, EXPRESS YOUCAT - Dessindi, Kristhalia (CREDENDUM: Jurnal Pendidikan Agama, 2020)
The development of digital technology poses a challenge for the Church to find new ways to spread the faith to Generation Z. The media is a good supporter to facilitate the Church in proclaiming her teachings. In the era of the industrial revolution 4.0, digital media became one of the means of proclamation that the Church and pastoral activists could use to spread faith to Generation Z. The author's exploration of generation Z led the author to be interested in the theme "Digital Media as a New Agora for Public Service". Based on the results of the literature study, it was concluded that digital media was able to connect with them. For Generation Z, digital media can be an alternative means of proclaiming the Church today, especially during a pandemic. Their connection to digital media makes the Church need to think of new ways of preaching that can also involve the laity, especially Generation Z, in its implementation, not only as digital content connoisseurs but also digital service content creators. As a suggestion, the author also synthesizes the learning theory of constructivism and behaviorism that can be used in the preaching process and in assisting the formation of faith for Generation Z which is also used in the YOUCAT Indonesia know, share, meet and express reporting method.